Linguistic challenges and English writing proficiency among senior high school students in Portovelo public school - Pupiales Chuquin, Ector Geovanny; Lizaldes-E, Orlando Vicente (JEELS (Journal of English Education and Linguistics Studies), 2025)
Writing in English as a Foreign Language (EFL) continues to pose significant challenges for senior high school students, primarily due to linguistic difficulties in writing skills. This study aimed to identify the linguistic challenges that affect students´ writing skills and to determine the correlation between these challenges and their performance on an English writing proficiency test. By using quantitative correlational research, 81 third-year students from a public high school were instructed to fill out a 30-item proficiency test that assessed their writing proficiency and a structured questionnaire to assess their linguistic challenges. However, the correlation analysis showed weak relationships between linguistic challenges and overall writing proficiency. This indicated that although linguistic competence impacts writing, it is not the only factor affecting students’ performance. Finally, overcoming EFL writing difficulties requires a comprehensive teaching approach that supports linguistic, psychological, and environmental factors. The implication of this finding is that writing instruction should not focus solely on correcting grammar or vocabulary errors but should include broader instructional strategies that address cognitive and contextual. aspects of writing.